Problems in primary education - Dearden, R. F. (London : Boston : Routledge & K. Paul, 2012)
The first part of the book discusses aims, who should determine them and how they might be determined. The second part discusses some more specific topics of learning and teaching, such as learning how to learn, the integrated day and the use of competition. The author distinguishes three broad levels of thought in looking at schools: the details of choice and decision; the general principles which are, or ought to be, guiding that detailed practice; and the theoretical commentaries on the guiding principles available from the various disciplines which constitute the study of education.
Includes bibliographical references and index.
Keywords: Education, Elementary -- England; Education, Elementary